35.8k views
5 votes
3-^1 x (4 x 6) x 2-^3

3-^1 x (4 x 6) x 2-^3-example-1
User Joealba
by
5.3k points

2 Answers

5 votes

3^-1 = 1/3

2^-3 = 1/8

(4.6) = 24

24 × 1/8 × 1/3 = 1

User Goji
by
4.9k points
6 votes


\huge{ \boxed{ \mathbf{ \blue{Problem:-</p><p>}}}}


\bold{ {3}^( - 1 \ ) (4 * 6) * {2}^( - 3) }


\huge{ \boxed{ \bf{ \blue{Solution:-}}}}


\bold{ {3}^( - 1)(4 * 6) * {2}^( - 3) }


= \bold{ (1)/(3)^(1) (4 * 6) * { (1)/(2)^(3) } }


= \bold{ (1)/(3) * 24 * (1)/(8) }


\bold{= 1}

Hope it's helpful

User Mrchief
by
4.3k points